PENGARUH SOCIAL MEDIA MARKETING, INFLUENCER MARKETING DAN BRAND TRUST TERHADAP BRAND LOYALTY PADA PRODUK FASHION DI SHOPEE - Zahrani, Ameylia; Wuryan, Sophiyanto; Muniroh, Muniroh (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study examines the influence of social media marketing, influencer marketing, and brand trust on brand loyalty in fashion products marketed through the Shopee platform. The study is driven by the intensifying competition in the e-commerce sector, where trust and loyalty are critical for brand differentiation and sustainability. A quantitative method was employed through online surveys, gathering data from 140 active Shopee users who also follow social media influencers. Data analysis was conducted using multiple linear regression via SPSS. The results reveal that all three variables—social media marketing, influencer marketing, and brand trust—positively and significantly affect brand loyalty both simultaneously and partially. Among them, social media marketing has the most dominant influence. These findings highlight the importance of effective digital engagement strategies, influencer credibility, and trust-building mechanisms in enhancing customer loyalty within online fashion commerce.Keywords : social media marketing, influencer marketing, brand trust, brand loyalty